Effects of COVID-19 Policy on Air Quality in Lagos State, Nigeria - Floyd Amaechi, Chika; Enuneku, Alex; Amadi , Ugochinyere Stephanie; Okoduwa, Akus Kingsley (Applied Environmental Research, 2024)
The decrease in air quality has been a major concern in the world for decades, and it has continued to worsen with toxic gases accumulating at exponential rates. The atmosphere has been heavily polluted as a result of anthropogenic activities, and these activities were greatly reduced during the COVID-19 pandemic when a lockdown policy was imposed. The study area, Lagos, is the state in Nigeria with the highest population count, making it most susceptible to the spread of the coronavirus and, as such, having the strictest policy regulations. This study seeks to evaluate the effects of the COVID-19 lockdown policy on air quality in Lagos State. The study adopted geographic information systems (GIS) and remote sensing techniques. Goggle Earth Engine (GEE) and Sentinel 5P (S5P) TROPOMI dataset were used to obtain results for carbon monoxide (CO), sulphur dioxide (SO2), aerosols (particulate matter), and nitrogen dioxide (NO2) through JavaScript coding for the year before the lockdown (2019), the year of the lockdown (2020), and the year after the lockdown (2021). Results from the study revealed that the year 2020 had lower concentrations of aerosols and NO2, which increased in 2021 when human and vehicular activities were back to normal. SO2 and CO concen-trations were higher in the year 2020 than in year 2019 and 2021, suggesting that the COVID-19 lockdown was loosely implemented. It is recommended that policymakers invest in green technologies such as solar systems to minimize emissions, enforce strict emission standards for industries and vehicles to limit the release of air pollutants.